ISO 9000 and its effect on the financial performance of publicly listed certified companies. - Phoon, Sok Fun. (2008)
This research aims to explore the impact of the ISO 9000 certification on a company's financial performance. The relative performance of ISO 9000 certified companies before and after certification is examined. The limitations associated with the utilization of median comparison are eliminated by the design of a carefully matched benchmark. Subsequently, the performance of these benchmarked companies is compared with the ISO 9000 certified ones.